Succession in family farming: gender and future perspectives (Research, Society and Development, 2021)
The succession processes in rural properties, in particular, in family farming, has taken priority status among the themes that involve the rural environment. The present study was carried out in the extreme west of the state of Santa Catarina, between the years 2016 and 2017, when 268 farmers were interviewed. In addition to the objective of recording and discussing data related to succession, gender and generational processes, the research was also carried out as a didactic tool for agricultural sciences courses in the region. The study recorded the desire, regardless of gender, of 5.5% of young people to break connection with agriculture in their future and not participate in the succession processes. Result that opposes the point of view of the parents, who express a gender distinction in the succession role, where 72.4% relates the male gender to such, while for the female gender the desire of 94% of fathers and mothers is that the daughters, respectively, get married and / or live in the city. The study points out the importance of actions involving the parents of rural youth in succession and gender issues that are increasingly urgent in the possible future of family farming.